Drotrecogin Alpha (Activated) in Two Patients with the Hantavirus Cardiopulmonary Syndrome - Robert C McDermid; RT Noel Gibney; Ronald J Brisebois; Neil M Skjodt (Canadian Respiratory Journal)
Hantavirus cardiopulmonary syndrome (HCPS) is associated with rapid cardiopulmonary collapse from endothelial injury, resulting in massive capillary leak, shock and severe hypoxemic respiratory failure. To date, treatment remains supportive and includes mechanical ventilation, vasopressors and extracorporeal membrane oxygenation, with mortality approaching 50%. Two HCPS survivors initially given drotrecogin alpha (activated) (DAA) for presumed bacterial septic shock are described. Vasoactive medications were required for a maximum of 52 h, whereas creatinine levels and platelet counts normalized within seven to nine days. Given the similar presentations of HCPS and bacterial septic shock, empirical DAA therapy will likely be initiated before a definitive diagnosis of HCPS is made. Further observations of DAA in HCPS seem warranted.